1970
DOI: 10.1111/j.1365-2141.1970.tb06981.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Slowly Proliferating Cells in Rat Bone Marrow during. Regeneration following Hydroxyurea

Abstract: Summary. Rats were labelled with 3H‐thymidine (3H‐TdR) in utero and for 6 weeks after birth to obtain 100% labelling of all the cells in the animals. 6 weeks after the last 3H‐TdR injection only cytokinetically resting cells were still labelled. In bone marrow these were cells of the bone marrow matrix and a fraction of small bone marrow lymphocytes. At this time the effect of hydroxyurea (HU) on bone marrow and especially on the resting cells of this organ was studied. Animals which had received 4x 500 mg HU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

1972
1972
1982
1982

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 17 publications
(8 reference statements)
1
6
1
Order By: Relevance
“…Therefore, the interpretation would again be that only few, if any, of these cells did react to antigen stimula tion. Similar findings could be demonstrated under regeneratory demand [6,7]. However, the reticular cells and histiocytes of the spleen showed a decrease of their labelling index without a marked diminuation of the mean grain count.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Therefore, the interpretation would again be that only few, if any, of these cells did react to antigen stimula tion. Similar findings could be demonstrated under regeneratory demand [6,7]. However, the reticular cells and histiocytes of the spleen showed a decrease of their labelling index without a marked diminuation of the mean grain count.…”
Section: Discussionsupporting
confidence: 74%
“…In the spleen of mice only 0.10-0.20 immuno competent cells for a specific antigen could be detected per 10° cells [1,2,8], Therefore, the conclusion would be that under immune stimulation, the mass of long-living lymphocytes does not react in the sense of a trans formation or proliferation. In contrast to that behaviour, as could be shown in previous work, the mass of bone-marrow lymphocytes did react under regeneratory stimulus [6,7].…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…[1] and T alley and Vaitkevicius [17] who observed chromo somal abnormalities in bone marrow red cell and white cell precursors in patients treated with Ara-C, with the finding of R u sco n i el al. [16] of incor poration of D into rat bone marrow cells, with the demonstration by M illa r and B la c k ett [11] of sensitivity to D of rat bone marrow erythropoietin response cells and maturing erythroid cells, and with the destruction of pro liferating bone marrow of HU-treated rats shown by Bohne et al [3], Similarly, the decreased lobulation of M-III nuclei found in rats treated with Ara-C or D may reflect an impairment of endomitosis resulting from the action of these drugs on megakaryoblasts' DNA and/or its synthesis. Bell et al [1] found abnormally large red cell precursors with gigantic indented nuclei having irregular borders in Ara-C treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of various cytotoxic agents on hema topoietic precursor cells in rat bone marrow was studied by several investi gators [3,11,14,16], It has been found that D is taken up by rat bone marrow elements [16] and affects erythroid precursors [11] and that HU destroys proliferating rat bone marrow cells [3], To our knowledge no reports have appeared on the effects of Ara-C, D and HU on bone marrow mega karyocytes in the rat. The present study was undertaken to investigate the effects of these drugs on this cell line in this animal.…”
Section: Introductionmentioning
confidence: 99%